Negative effects of zearalenone on reproductive productivity in dairy cattle - Dogan, Veysel; Dal, Sevval Damla (Kastamonu Üniversitesi, 2022)
Mycotoxins, which are produced by different fungi reproduced in feed materials worldwide, have adverse effects on animal and human health. Zearalenone (ZEN) is a common mycotoxin, secreted from Fusarium spp. that may cause reproductive problems in animal species due to its non-steroidal estrogenic feature. The sensitivity of livestock to ZEN differs based on the species and sexuality. Cows are considered less sensitive to ZEN, however, there is limited information about adverse effects caused by ZEN. In this article, we aimed to review the effects of ZEN on cows in negative energy balance.
Keywords: Veterinary Surgery; Zearalenone; -zearalenol -zearalenol; negative energy balance; dairy cattle; Veteriner Cerrahi; 2. Zero hunger; 3. Good health